Higher education for sustainable development in Flanders: balancing between normative and transformative approaches. Issue 9 (2nd September 2018) - Lambrechts, Wim; Van Liedekerke, Luc; Van Petegem, Peter
Abstract: This paper provides critical reflections on higher education for sustainable development (HESD) from a philosophical perspective. A theoretical framework is developed, based on John Dewey's thoughts on the aim of democracy and the critical role of education herein, and with specific focus on two constructs: 'initiative and adaptability' and 'values and virtues'. This theoretical framework is used to analyze HESD in Flanders, from a historical and socio-political perspective. The Flemish case shows a gradual evolution from a focus on environmental management on campus, followed by a normative interpretation of what HESD should look like, and a more transformative approach in light of citizenship and democratic ideals. The case also shows considerable exchange of information between Flanders and the Netherlands, in which Dutch models and instruments were used in the Flemish context. The philosophical perspective provides a theoretical grounding of the field of HESD, which enables us to further develop the field, with a specific focus on initiative and adaptability on the one hand, and the importance of a virtues perspective on the other.